Earlier post-operative hypocortisolemia may predict durable remission from Cushing's disease. Issue 3 (March 2018) - Ironside, Natasha; Chatain, Gregoire; Asuzu, David; Benzo, Sarah; Lodish, Maya; Sharma, Susmeeta; Nieman, Lynnette; Stratakis, Constantine A; Lonser, Russell R; Chittiboina, Prashant
Abstract : Context: Achievement of hypocortisolemia following transsphenoidal surgery (TSS) for Cushing's disease (CD) is associated with successful adenoma resection. However, up to one-third of these patients recur. Objective: We assessed whether delay in reaching post-operative cortisol nadir may delineate patients at risk of recurrence for CD following TSS. Methods: A retrospective review of 257 patients who received 291 TSS procedures for CD at NIH, between 2003 and 2016. Early biochemical remission (serum cortisol nadir <5 μg/dL) was confirmed with endocrinological and clinical follow-up. Recurrence was detected by laboratory testing, clinical stigmata or medication dependence during a median follow-up of 11 months. Results: Of the 268 unique admissions, remission was recorded in 241 instances. Recurrence was observed in 9% of these cases with cortisol nadir ≤5 μg/dL and 6% of cases with cortisol nadir ≤2 μg/dL. The timing of hypocortisolemia was critical in detecting late recurrences. Morning POD-1 cortisol <3.3 μg/dL was 100% sensitive in predicting durable remission and morning POD-3 cortisol ≥18.5 μg/dL was 98.6% specific in predicting remote recurrence. AUROC analysis revealed that hypocortisolemia ≤5 µg/dL before 15 h (post-operative) had 95% sensitivity and an NPV of 0.98 for durable remission. Serum cortisol level ≤2 µg/dL, when achieved before 21 h, improved sensitivity to 100%. Conclusions: In our cohort, early, profound hypocortisolemia could be used as a clinical prediction tool for durable remission. Achievement of hypocortisolemia ≤2 µg/dL before 21 post-operative hours appeared to accurately predict durable remission in the intermediate term.